Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2006)
At Every seminar, Conference, we discuss matters of current interest, debate, deliberate, have exchange of views and, generally, arrive at a consensus. Then, we put this consensus in a form of resolution and pass it, may be unanimously or by majority. What happens to these resolutions? What happens to the energy, time, heated discussions, involved in all this process of getting these resolution passed? Nobody knows, nobody bothers to ask. Everything evaporates and is almost forgotten . This is going on for years and years.